Fabrication Of A Sealed Off Co2 Gas Laser - Iqbal, Shahid (2002)
This study consists of two parts. In the first part a mathematical model for sealed-off CW C02 laser is developed. The developed model based on the four-temperature model and is developed by modifying the steady state C02 laser model presented by Scott et al. [28]. The equations relating the modes energy verses intra cavity optical intensity in equilibrium are used for modelling. An energy balance equation involving the terms of power loading, optical power removed and power loss in the form of the heat removed through the laser tube walls is derived. The variation in the output power as the power loading is varied is predicted using the model. The predicted results of output power respective to the power loading are found to show the similar response as found experimentally. In second part a sealed off CO2 laser is fabricated using custom-made air-cooled laser tube with internal mirror design and power supply. Both laser tube and power supply are placed in custom made wooden box. The box is especially built for housing the laser components. The cooling of the laser tube and power supply is achieved by using four fans. An electronic circuitry to measure the laser tube temperature is developed. The laser is operated both in continuous wave mode as well as in pulse mode. A maximum power of 12.2 Watts is measured during continuous wave mode operation at a current of 14 mA. The output power is found to decrease with further increase in current. During pulsed operation, the energy of the optical pulses is found to be maximum at 100 Hz and a decrease in the pulse energy is detected with further increase in the pulse repetition rate. The temperature is found to be the major factor effecting the laser power. Without fans the temperature of the laser tube is found to reach to 85 ° C in 10 minutes. The output power is also found to drop to zero at 85 ° C . However with running fans, the maximum temperature that laser tube wall could reach is found to be 55 °C independent of the time. The laser power at 55 ° C is found to be 9 Watts. The threshold and steady state voltage at the laser tube electrodes is also measured and is found to be 15640 volts and 8160 volts respectively. The C02 laser is useful for industrial drilling, welding, cutting and for air ionization or discharge applications. The purpose of this research is to design 14 Watt CO2 gas laser for air ionisation and high voltage sphere gap triggering in the subsequent research.